2008
DOI: 10.1158/1055-9965.epi-07-2947
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the Selenoenzyme Genes and Risk of Advanced Distal Colorectal Adenoma

Abstract: Background: Epidemiologic and animal studies provide evidence for a chemopreventive effect of selenium on colorectal cancer, which may be mediated by the antioxidative and anti-inflammatory properties of selenoenzymes. We therefore investigated whether genetic variants in selenoenzymes abundantly expressed in the colon are associated with advanced colorectal adenoma, a cancer precursor. Methods: Cases with a left-sided advanced adenoma (n = 772) and matched controls (n = 777) screen negative for polyps based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
83
1
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 105 publications
(90 citation statements)
references
References 71 publications
5
83
1
1
Order By: Relevance
“…Variants of a SNP in the promoter of the selenoprotein P gene (SEPP1) were not associated with altered risk of CRC [1], but a more recent study indicated that three variants in SEPP1 and one in the thioredoxin reductase 1 gene TXNRD1 showed an association with risk of adenoma [22]. In addition, a relatively small case-control study in the United Kingdom showed an association of the C variant of rs713041 in GPX4 with increased risk of CRC [3].…”
Section: Introductionmentioning
confidence: 99%
“…Variants of a SNP in the promoter of the selenoprotein P gene (SEPP1) were not associated with altered risk of CRC [1], but a more recent study indicated that three variants in SEPP1 and one in the thioredoxin reductase 1 gene TXNRD1 showed an association with risk of adenoma [22]. In addition, a relatively small case-control study in the United Kingdom showed an association of the C variant of rs713041 in GPX4 with increased risk of CRC [3].…”
Section: Introductionmentioning
confidence: 99%
“…Over-expression of GPX-1 is associated with a wide range of effects, including the prevention of apoptosis, the protection against toxicity and the reduction of DNA damage (Zhuo, et al, 2009). Given human epidemiological data indicating significant associations between polymorphisms in GPx-1 and the risk of several cancer types due to the important biological activities of the essential trace element selenium are mediated through the function of selenoenzymes (Ichimura, et al, 2004;Hu & Diamond, 2003;Mak, et al, 2006;Choi, et al, 2007;Peters, et al, 2008). In this article we show the relationship between the presence of the Pro198Leu variant of the GPX-1 gene and its association with the risk of developing bladder cancer.…”
Section: Resultsmentioning
confidence: 78%
“…In the murine intestine, GPx4 mRNA is one of the most abundant selenoprotein transcripts (8); genetic variant analysis of the human GPX4 gene links it to malignant disease risk in the gastrointestinal tract (9,11). Investigation of intestinal GPx4 has so far been limited to the mRNA level (33,36) and to the measurement of GPx4 activity in mouse tissue homogenates (44).…”
Section: Discussionmentioning
confidence: 99%
“…A constant level of GPx4 mRNA during periods of limited selenium availability as against the concomitant degradation of other GPx isoforms such as GPx1 reflects the high ranking of GPx4 in the so-called selenoprotein hierarchy (32) and argues for an important role of this protein in enterocytes. Intriguingly, a function of GPx4 as a candidate mediator of selenium-dependent chemoprevention in the colon arises from studies on the association of a single nucleotide polymorphism (rs713041) in the human GPX4 gene with colorectal adenoma and colorectal cancer risk (9,11,18). The enzymatic capacity of GPx4 extends beyond those of other hydroperoxide-degrading GPx isoforms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation